Sound Moves A Roehampton conference attended - Still, Jonathan (Dance Books Ltd., Alton,Hampshire (UK), 2006)
A Roehampton conference attended by Jonathan Still. PALABRAS CLAVE: dance and music, Stephanie Jordan, Marian Smith.